BURKITT’S LYMPHOMA IN KIDNEY: A RARE ENTITY. - Riaz, Muhammad Mohsin; Khaqan, Arous; Sabir, omer (Pakistan Journal of Kidney Diseases, 2021)
Burkitt’s Lymphoma is an aggressive form of Non-Hodgkin’s Lymphoma, with higher incidence in children comprising 30% of pediatric lymphoma. The hallmark of which is a translocation involving c-MYC gene on chromosome 8. Burkitt’s Lymphoma comprises of 6.35% of all lymphoma cases in Pakistan, with male predominance. Lymphoma rarely presents as a primary pathology of acute kidney injury. Burkitt’s lymphoma in adult population is uncommon and few cases have been reported where Burkitt’s lymphoma presents as a cause of acute kidney injury. There are three epidemiological subtypes Endemic (African), sporadic (non-endemic) and immunodeficiency related. Sporadic cases dominate amongst others in Pakistan.